Experience of Managing Countertransference Through Self-Guided Imagery in Meditation Among Healthcare Professionals - Aasan, Olaug Julie; Brataas, Hildfrid Vikkelsmo; Nordtug, Bente (Frontiers in Psychiatry, 2022)
Introduction: As a part of the therapeutic relationship, a significant, well-established predictor of outcomes in psychiatric health care, health care professionals’ emotional reactions to patients may affect treatment outcomes. Aim: The aim of our study was to explore and describe health care professionals’ experiences with managing countertransference using skills from a training program on self-guided imagery in meditation (SIM). Method: Following an exploratory descriptive design, we conducted qualitative interviews with 10 health care professionals who care for patients with mental illness and subjected the collected data to thematic content analysis. Results: Participants reported that SIM had helped them to manage countertransference and had prompted changes that we categorized into three themes: managing personal vulnerability, setting clearer boundaries, and practicing self-care. Conclusion: The results suggest that by cultivating well-being and dealing with unresolved inner conflicts, SIM can help health care professionals to manage countertransference.